Developing a Sustainable Procurement Action Plan for Public Sector in Ajman - Al Abdooli, Aisha Mohamed (2011)
Sustainability, sustainable development (SD) and sustainable procurement (SP) are important topics on many countries’ agenda worldwide. The concept of sustainability is formulated around meeting present generation needs without compromising future generation needs. Depletion of natural resources, affecting biodiversity and increasing poverty are common challenges faced by many communities all around the world. Therefore, it is really important to address sustainability aspects whole community’s activities. Public sector has significant spending rates for procuring different projects and services, which makes it among key players in market. If it used its purchasing power toward affecting market’s attitude, then for sure that will be a key success factor for implementing SP aspects. If such concept can be implemented in public sector, then it can be adopted smoothly in other sectors as well. The aim of this dissertation was to develop an action plan to implement SP at Ajman’s public sector. Drivers, barriers for SP, diffusion mechanisms and the impact from the Political, Environmental, Social, Technological, Economical and legislative aspects were investigated to serve dissertation’s aim. Since SP concept is not common in Ajman, survey method could not be used as responds level and quality will neither be accurate nor representative. Case studies, interviews and focused group discussion were used instead. Among the list of different drivers and barriers affecting SP implementation at public sector, the following factors were playing potential role in Ajman’s public sector, which are government support, financial aspect, right understanding of SP, necessary legislations and necessary awareness campaigns. There were many sustainable initiatives implemented at the case studies’ organizations. However, these initiatives were not incorporated in an integrated sustainable scheme. This dissertation is showing that there is a potential readiness in Ajman to accept SP implementation. Implementation needs to be supported by necessary legislations, necessary top management commitment, intensive training programs for employees to build required level of skills, intensive awareness campaigns for all community members and intensive educational programs for students at all academic level.